Base‐mediated Benzannulation Reactions for the Synthesis of Densely Functionalized Aryl α‐Keto Esters. Issue 8 (13th July 2021) - Jia, Qianfa; Yin, Guoliang; Lan, Yunfei; Lin, Yinhe; Ren, Qiao
Abstract: A novel and straightforward strategy for the construction of versatile densely functionalized aryl α‐keto esters is disclosed through a one‐pot and efficient [4+2] benzannulation reaction of α‐cyano‐β‐methylenones and ynediones, which could be synthesized easily from the corresponding starting materials. This protocol features high yield, mild metal‐free reaction condition, high atom economy, high functional‐group tolerance, easy handing and gram‐scale synthesis. Abstract : An effective approach to construct densely functionalized aryl α‐keto esters under mild conditions has been reported. A broad range of multi‐substituted benzenes were prepared in good to excellent yields and many useful functional groups could be tolerated.